The legacy of Rosa Luxemburg, Oskar Lange and Michał Kalecki : volume 1 of essays in honour of Tadeusz Kowalik - Bellofiore, Riccardo; Karwowski, Ewa.; Toporowski, Jan.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Rosa Luxemburg, Oskar Lange and Micha? Kalecki made important contributions to twentieth century political economy that guided the thinking of their student Tadeusz Kowalik. These contributions are re-examined by renowned economists, highlighting the common themes in their political economy and the neglected aspects of their work.
Keywords: Science